The Influence of Compensation on the Performance of Program Keluarga Harapan (Pkh) at The Karawang District Social Services - Arieyanti Syamputri; Sonny Hersona; Hartelina (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of compensation on the performance of the Family Hope Program (PKH) facilitator at the Karawang Regency Social Service. The method used is explanatory research with a sample of 35 people. The analysis technique uses statistical analysis with correlation, regression, determination and hypothesis testing. The results of the research on the Performance of the Family Hope Program Facilitator (PKH) at the Karawang Regency Social Service. Shows a significant influence value of 8.67 so that it is considered to have contributed to the compensation received. Compensation given to the companion of the Family Hope Program simultaneously has a positive and significant effect on employee performance. This study aims to determine the effect of compensation on the performance of the Family Hope Program (PKH) facilitator at the Karawang Regency Social Service. compensation as a form of appreciation for the achievement of company or institutional activities to employees for the contributions and dedications given to the company or institution. Performance which is all activities of a company or institution, including employees in it is the spearhead of achieving or not achieving the vision and mission of an institution or company. The method used is explanatory research with a sample of 35 people. The analysis technique uses statistical analysis with correlation, regression, determination and hypothesis testing. The results of the research on the Performance of the Family Hope Program Facilitator at the Social Service of Karawang Regency from 35 samples obtained results of 0.663 or 66.3% which shows that the effect of compensation on employee performance is still not optimal. Compensation for the Family Hope Program facilitator has a contribution to performance that can be interpreted as a form of material appreciation. Compensation given to the companion of the Family Hope Program simultaneously has a positive and significant effect on employee performance..